Exacerbation of secondary trigeminal neuralgia due to osteomyelitis in a case of Romberg facial hemiatrophy - Florin Popovici; Athena Mergeani; Dan Popescu; Florina Antochi (Romanian Journal of Neurology, 2011)
Progressive facial hemiatrophy or Romberg syndrome, is a sporadic disease of unknown etiology characterized by progressive and self limited shrinking and deformation of one hemiface accompanied by various neurologic complication, including trigeminal neuralgia. We present the case of a 31-year-old Caucasian female with exacerbation of a left trigeminal neuralgia two weeks after a dental extraction. The severe pain was due to osteitis of the left mandible and a fracture through the 38 alveola. After removing the necrotic tissue and mandibulo-maxilary fixation the evolution was favorable with no signs of infection or wound dehiscence and the symptoms of pain were relieved.